Penerapan Metode Case Based Reasoning Pada Pengembangan Aplikasi Recipe Recommendation Berbasis Android - Kurnia Muludi; Didik Kurniawan; Lia Atika Rani (Universitas Lampung, 2016)
Recipes are needed as a means to guide people when preparing ingredients for cooking, making and serving food. These days there are more and more smartphone users and Android is the most dominant operating system. Android based smartphone is very easy to use, so many people choose it. Case Based Reasoning (CBR) is a problem solving approach by emphasizing the role of prior experience. New problems can be solved by utilizing toward similar problems that have been solved before. In this study, we design and build a Recipe Recommendations Apps for Android and applying Case-Based Reasoning method. This application provide recommendations of any recipes of Indonesian Foods that can be made by inputting available ingredients and step by step of cooking and the way they are presented. This evaluation show that the application successfully constructed and useful for user.